Investors’ Trade Size and Trading Responses Around Earnings Announcements: An Empirical Investigation. - BHATTACHARYA, Nilabhra (Institutional Knowledge at Singapore Management University, 2001)
Prior research suggests that the earnings expectations of a segment of the market can be described by the seasonal random‐walk model. Prior research also provides evidence that less wealthy and less informed investors tend to make smaller trades (small traders) than wealthier and betterinformed investors (large traders). I hypothesize that it is the earnings expectations of small traders that are associated with predictions from the seasonal random‐walk model. By directly analyzing the trading activities of small and large traders, this study provides evidence that is largely consistent with the hypotheses. Specifically, small traders' trading response around earnings announcements is increasing in the magnitude of seasonal random‐walk forecast errors, even after controlling for absolute analyst forecast errors, contemporaneous price changes, and market‐wide trading. Supplementary analysis reveals that this effect is largely confined to firms with relatively impoverished information environments (i.e., smaller firms and firms with little to moderate analyst following).